2018
DOI: 10.1016/j.ihj.2018.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic use of carvedilol to prevent ventricular dysfunction in patients with cancer treated with doxorubicin

Abstract: ObjectiveDeterioration in ventricular function is often observed in patients treated with anthracyclines for cancer. There is a paucity of evidence on interventions that might provide cardio-protection. We investigated whether prophylactic use of carvedilol can prevent doxorubicin-induced cardiotoxicity and whether any observed effect is dose related.MethodsA prospective, randomized, double-blind study in patients treated with doxorubicin, comparing placebo (n = 38) with different doses of carvedilol [6.25 mg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 13 publications
0
26
0
1
Order By: Relevance
“…The analysis included 10 studies [13][14][15][16][17][18][19][20]25,26 with 385 patients in the beta-blocker group and 384 control patients. The mean LVEF difference between the beta-blocker group and the control group was 2.57%, 95% CI (0.63-4.51), P = 0.009.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The analysis included 10 studies [13][14][15][16][17][18][19][20]25,26 with 385 patients in the beta-blocker group and 384 control patients. The mean LVEF difference between the beta-blocker group and the control group was 2.57%, 95% CI (0.63-4.51), P = 0.009.…”
Section: Resultsmentioning
confidence: 99%
“…The most frequent tumour disease was breast cancer followed by haematological malignancies. Eight eligible trials assessing beta-blockers (carvedilol, nebivolol, bisoprolol, and metoprolol), [13][14][15][16][17][18][19][20] four studies assessing ACE inhibitors/ARBs (enalapril, telmisartan, candesartan, and perindopril), [21][22][23][24] and two studies assessing beta-blockers and ACE inhibitors/ARBs in parallel arms 25,26 were identified ( Table 1). The sample sizes in groups were rather low, ranging from n = 18 to n = 103.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As the cardiotoxic mechanism of anthracyclines involves inducing oxidative stress and mitochondrial dysfunction, protective agents that are able to lower the production of ROS or lower the workload of the heart during anthracycline treatment may be beneficial to reduce anthracycline-induced cardiotoxicity. Factors that may reduce oxidative stress in the heart, such as statins and natural antioxidants, and compounds that reduce the workload of the heart, such as angiotensin-converting-enzyme (ACE) inhibitors and beta-blockers, have been combined with anthracyclines in clinical trials, with mixed success (66)(67)(68)(69)(70)(71)(72)(73)(74)(75)(76)(77). As far as known, these compounds have never been tested in hPSC-cardiomyocytes for assessment of their direct cardioprotective potential, even though reducing oxidative stress in particular can be readily modeled in vitro.…”
Section: Protective Agents To Alleviate Cardiotoxicitymentioning
confidence: 99%
“…Carvedilol (CRV) ( Figure 1 ) is a non-selective blocker of α and β adrenergic receptors, and has been extensively used for the treatment of hypertension and congestive heart failure. CRV oral bioavailability ranges from 20% to 35% owing to its low water solubility and increased fast metabolism [ 1 , 2 , 3 ]. To circumvent its unsatisfactory biopharmaceutical properties, CRV has been incorporated in different types of drug delivery systems, e.g., nanoemulsions [ 4 ], solid-state cyclodextrin complexes [ 5 ], solid dispersions [ 6 ], transdermal vehicles [ 7 ], and supramolecular hydrogels [ 8 ].…”
Section: Introductionmentioning
confidence: 99%